(untitled) (Research, Society and Development, 2020)
The use of drugs by healthy people to improve the brain functioning and enhance the cognitive performance might be called as pharmacological cognitive enhancement or intellectual doping. In Brazil, one of the most common drugs used for this purpose is the Methylphenidate Hydrochloride, which is marketed as Ritalina (Ritalin) or Concerta. This article aimed to understand, through a literature review, how methylphenidate hydrochloride has been used in the pharmacological cognitive enhancement and the relationship of this phenomenon with social medicalization. It is known that these drugs have the immediate effect of increasing concentration, but in the long term, they may cause growth suppression, increasing the blood pressure, psychotic episodes, etc. Even so, they have been used by academics with the purpose of increasing their production capacity and meeting deadlines and targets. Considering the increasing of the fans of this pratice and the facilitation of access to this medicine, it is necessary to go deep into the understanding of this phenomenon.